(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article examines Will Kymlicka’s defense of minority rights within the framework of liberal political theory, arguing that the recognition of national minorities is fully compatible with universal liberal principles. The discussion highlights Kymlicka’s effort to restore the concept of national minorities to contemporary debates on justice and multiculturalism, while distinguishing his position from those of Charles Taylor, David Miller, and Margaret Canovan. The analysis further explores the historical and political limitations of Kymlicka’s argument, particularly regarding the neglect of Marxist perspectives on nationality and the practical challenges of applying minority rights in different political contexts, including Central and Eastern Europe. It concludes that Kymlicka’s work makes a significant contribution to liberal theory by demonstrating that minority rights can strengthen rather than undermine democratic equality, even if important theoretical and political questions remain unresolved. This abstract is generated with artificial intelligence.